Schooling and Labor Market Impacts of a Natural Policy Experiment - Patrinos, Harry Anthony (World Bank, Washington, D.C., 2013)
The authors use a nationally representative household survey to estimate returns to schooling in Venezuela from instrumental variables based on a supply-side intervention in the education market. These estimates apply to a subgroup of liquidity-constrained individuals, in the spirit of the Local Average Treatment Effect (LATE) literature. Returns to schooling estimates which apply to a subgroup of individuals affected by the policy intervention may be more interesting from a policy perspective than the return to the "average" individual. The authors use an instrument based on the 1980 education reform (the Organic Law of Education) which provided for nine years of compulsory basic education. They also obtain alternative estimates using father's education as an instrument, in an attempt to derive high and low estimates of returns to schooling in Venezuela. The estimates are consistent with recent findings suggesting that the effect of education, at least for certain subgroups affected by a policy intervention, is as large, or larger than what is suggested by OLS estimates.